Association of NOS1 gene polymorphisms with cerebral palsy in a Han Chinese population: a case-control study - Ting Yu; Lei Xia; Dan Bi; Yangong Wang; Qing Shang; Dengna Zhu; Juan Song; Yong Wang; Xiaoyang Wang; Changlian Zhu; Qinghe Xing (BMC, 2018)
Abstract Background Cerebral palsy (CP) is the leading cause of motor disability in children; however, its pathogenesis is unknown in most cases. Growing evidence suggests that Nitric oxide synthase 1 (NOS1) is involved in neural development and neurologic diseases. The purpose of this study was to determine whether genetic variants of NOS1 contribute to CP susceptibility in a Han Chinese population. Methods A case-control study involving 652 CP patients and 636 healthy controls was conducted. Six SNPs in the NOS1 gene (rs3782219, rs6490121, rs2293054, rs10774909, rs3741475, and rs2682826) were selected, and the MassARRAY typing technique was applied for genotyping. Data analysis was conducted using SHEsis online software, and multiple test corrections were performed using SNPSpD online software. Results There were no significant differences in genotype and allele frequencies between patients and controls for the SNPs except rs6490121, which deviated from Hardy-Weinberg equilibrium and was excluded from further analyses. Subgroup analysis revealed differences in genotype frequencies between the CP with neonatal encephalopathy group (CP + NE) and control group for rs10774909, rs3741475, and rs2682826 (after SNPSpD correction, p = 0.004, 0.012, and 0.002, respectively). The T allele of NOS1 SNP rs3782219 was negatively associated with spastic quadriplegia (OR = 0.742, 95% CI = 0.600-0.918, after SNPSpD correction, p = 0.023). There were no differences in allele or genotype frequencies between CP subgroups and controls for the other genetic polymorphisms. Conclusions NOS1 is associated with CP + NE and spastic quadriplegia, suggesting that NOS1 is likely involved in the pathogenesis of CP and that it is a potential therapeutic target for treatment of cerebral injury.